The practice of music in the "Libro de Apolonio" as an early case of Aristotelianism - Curtis, F (Brepols Publishers, 2017)
The Libro de Apolonio (c.1250) is a key witness of the medieval European practice of music . This version of the classical story of Apollonius of Tyre (2nd–3rd century CE), one of the first learned works of literature composed in the Castilian vernacular, extensively depicts music as a skill that demonstrates elevated understanding of world. In the Libro de Apolonio, virtuoso playing of a stringed instrument, namely the vihuela, fiddle, as accompanied by the voice, brings profound insight, transforming the lives of the principal characters at three crucial turning points in the narrative. The interest of the depiction of music in the Libro de Apolonio is thus not just diegetic or musicological. This clerical poem is imbued with the scholarship of the medieval curriculum i.e. the seven liberal arts. Within the hierarchy of the arts, music held an important position as one of the four higher, numeric subjects of the quadrivium, along with astronomy, arithmetic, and geometry, and exemplified all these higher arts . Mastery of the arts led to study of philosophy and theology, the ultimate disciplines for investigation of the world and the heavens. The practice of music in the Libro de Apolonio engages with contemporary philosophical and theological concerns and notably, as I shall argue, an Aristotelian worldview that profoundly challenges Christian doctrine.